Legal Writing in the United Kingdom: Impact on The Professional Development of Law Students - Ha, Do Thi (VNU Journal of Science: Legal Studies; Vol 40 No 4, 2024)
Legal writing is not only an essential skill for the career of those practicing law, but also an integral part of the training process at law schools in the UK. It is a mandatory subject in the undergraduate law degree (LLB) and a prerequisite course in the master's law program (LLM) at both intermediate and advanced levels. Known by various names and often combined with other subjects such as Legal Communication and Writing, Legal Research and Writing Skills, Legal Scholarship, etc., it typically spans two credits in the curriculum. This paper will analyze the teaching methods of Legal Writing Skills in UK law schools and the impact of legal writing on the professional development of law students. Using secondary sources, the paper will demonstrate how legal writing not only improves communication and argumentation skills of law students but also develops their critical thinking and deepens their understanding of the law. Moreover, legal writing poses significant challenges for learners, and innovative teaching methods are truly necessary to better prepare law students for their future professional development